A case of internal hernia in the pararectal fossa - Kozue Matsuishi; Seiya Saito; Mayuko Ohuchi; Yuki Kiyozumi; Jiro Nasu; Norihisa Hanada; Hideo Baba (Surgical Case Reports, 2023)
Abstract Background Internal hernias are relatively rare and difficult to diagnose. Diagnostic delays lead to the progression of strangulation. In particular, pararectal fossa hernias are extremely rare. We encountered a case in which internal hernia occurred in the pararectal fossa. Case presentation An 87-year-old woman was referred to our hospital because of persistent lower abdominal pain and vomiting. Contrast-enhanced computed tomography revealed findings of intestinal ischemia, such as closed loop formation with reduced contrast effect on the left side of the rectum in the pelvis. Strangulation small bowel obstruction was diagnosed, and emergency laparotomy was performed. The small intestine was found to invade the peritoneal reflection on the left side of the rectum. The patient was finally diagnosed with pararectal fossa hernia. The incarcerated small intestine was released with no bowel resection. The 4-cm hernia phylum was observed and closed by simple suture. The patient had a good postoperative course without recurrence. Conclusions We encountered a very rare case of internal hernia in the left pararectal fossa. Preoperative diagnosis of this disease is difficult, but it should nevertheless be considered in cases in which the cause of the intestinal obstruction is unknown.